Physiological Alterations due to Hepatotoxicity and the Protective Role of Cleome viscosa Linn Seed Extract in Experimental Animals. (29th December 2022) - Donkor, Addai-Mensah; Donkor, Martin Ntiamoah; Ahenkorah, Benjamin; Asare-Konadu, Kwadwo Asante; Asiedu, Emmanuel; Mosobil, Richard
Abstract : Liver ailment is a key public health menace, principally in developing nations. Quite a lot of medicinal florae have been identified to have liver shielding activities. The current study was designed to assess in vitro antioxidant and in vivo hepatoprotective activities of seed extracts of Cleome viscosa Linn. (Capparaceae). Phytochemical screening of C. viscosa seed ethanol extract was carried out. Free radical scavenging activity of crude seed extract of the plant was conducted using the DPPH assay method. DNA damage protection potential of the crude seed extract was carried out using extract of the genomic DNA nicking assay. Hepatoprotective activity of the crude seed extract of the plant was carried out based on CCl4 -induced liver damage in Wister albino rats. Serum biomarkers (aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), and total protein (TP)) were evaluated to find out the effect. Histopathological scrutiny was also carried out for all groups of rats to further confirm the discoveries. The phytochemical screening was positive for alkaloids, flavonoids, saponins, steroids, terpenes, tannins, and phenolic compounds in the seed extract. The antioxidant assay revealed that the ethanol crude extract of C. viscosa exhibited free radical scavenging activity with IC50 value of 17.82 ± 0.32 μ g/mL, and this was further confirmed by the DNA damage protection activity. Pretreatment of the rats with the crude extract of C. viscosa significantly reduced ALP (p < 0.05). The hepatoprotective activity of the seed extract was confirmed by histopathological studies. From this study, it can be concluded that the crude seed extract revealed antioxidant and hepatoprotective activities. For that reason, in the future, oral intake of C. viscosa seed extract as an adjunct natural therapy may be worthwhile to protect against liver failure-mediated inhibitory effects on reproductive function.